DNA ANALYSIS TECHNIQUES - Elhoudire, Roaa; Eljazwi, Fatima; Maftah, Salem (Faculty of pharmacy, 2019)
The DNA analysis techniques that make it possible to identify a suspect using a person’s unique genetic blue print have only been around since 1985. That's when Alec Jeffreys and his colleagues in England first demonstrated the use of DNA in a criminal investigation. Since then, DNA evidence has played a bigger and bigger role in many nations' criminal justice systems. It has been used to prove that suspects were involved in crimes and to free people who were wrongly convicted.
DNA ANALYSIS
Keywords: TECHNIQUES; DNA ANALYSIS